Search for tens of MeV neutrinos associated with gamma-ray bursts in Super-Kamiokande. (2nd July 2021) - ,; Orii, A; Abe, K; Bronner, C; Hayato, Y; Ikeda, M; Imaizumi, S; Ito, H; Kameda, J; Kataoka, Y; Kato, Y; Kishimoto, Y; et al.
Abstract: A search for neutrinos produced in coincidence with gamma-ray bursts (GRBs) was conducted with the Super-Kamiokande (SK) detector. Between December 2008 and March 2017, the Gamma-ray Coordinates Network recorded 2208 GRBs that occurred during normal SK operation. Several time windows around each GRB were used to search for coincident neutrino events. No statistically significant signal in excess of the estimated backgrounds was detected. The $\barν_e$ fluence in the range from 8 MeV to 100 MeV in positron total energy for $\barν_e+p→ e^{+}+n$ was found to be less than $\rm 5.07×10^5$ cm$^{-2}$ per GRB at a 90% confidence level. For all GRBs, upper bounds were obtained on the fluence as a function of neutrino energy. Additionally, for GRBs at known distances, upper limits were set for the neutrino energy emission at the GRB.